Inovasi Pelayanan Perpustakaan Universitas Muhammadiyyah Yogyakarta Selama Pandemi Covid-19 - Elok Nafilah; Sukaesih Sukaesih; Evi Nursanti Rukmana; Encang Saefudin (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2021)
The Covid-19 pandemic requires various fields to adapt. One area that has been affected is library services. Yogyakarta Muhammadiyyah University Library as one of the information service providers must make various adjustments so that it can still perform services effectively and efficiently. This study aims to determine the innovations made by the library of the Muhammadiyyah University Yogyakarta during the Covid-19 pandemic. The method used in this research is descriptive research with the process of collecting data through interviews. Data analysis in the form of collection, reduction, presentation, and drawing conclusions. The informant is a librarian from the Muhammadiyyah Yogyakarta library. The results showed that in adjusting library services to the Covid-19 pandemic, the Muhammadiyah University Yogakarta library made four innovations, namely offline services according to health protocols, online services using digital information technology in the form of websites and social media in helping users find the information needed, doing regular webinars, as well as collaborating between libraries. It is hoped that with these innovations the library can still perform services optimally.